Interleukin-19 Abrogates Experimental Autoimmune Encephalomyelitis by Attenuating Antigen-Presenting Cell Activation - Horiuchi, Hiroshi; Parajuli, Bijay; Komiya, Hiroyasu; Ogawa, Yuki; Jin, Shijie; Takahashi, Keita; Azuma, Yasu-Taka; Tanaka, Fumiaki; Suzumura, Akio; Takeuchi, Hideyuki (Frontiers in Immunology, 2021)
Interleukin-19 (IL-19) acts as a negative-feedback regulator to limit proinflammatory response of macrophages and microglia in autocrine/paracrine manners in various inflammatory diseases. Multiple sclerosis (MS) is a major neuroinflammatory disease in the central nervous system, but it remains uncertain how IL-19 contributes to MS pathogenesis. Here, we demonstrate that IL-19 deficiency aggravates experimental autoimmune encephalomyelitis (EAE), a mouse model of MS, by promoting IL-17–producing helper T cell (Th17 cell) infiltration into the central nervous system. In addition, IL-19–deficient splenic macrophages expressed elevated levels of major histocompatibility complex class II, co-stimulatory molecules, and Th17 cell differentiation–associated cytokines such as IL-1β, IL-6, IL-23, TGF-β1, and TNF-α. These observations indicated that IL-19 plays a critical role in suppression of MS pathogenesis by inhibiting macrophage antigen presentation, Th17 cell expansion, and subsequent inflammatory responses. Furthermore, treatment with IL-19 significantly abrogated EAE. Our data suggest that IL-19 could provide significant therapeutic benefits in patients with MS.